Desempeño del personal de enfermería de la Gerencia Regional de Salud - Red Maynas y cumplimiento de las metas del programa presupuestal orientado al desarrollo infantil temprano Loreto 2024 - Valles Ruiz, Enrriqueta Milagros (2025)
This research aimed to determine the relationship between the performance of nursing staff of the Regional Health Management-Red Maynas and the achievement of goals of the Budget Program oriented to early childhood development in the Loreto region during 2024. A quantitative, descriptive and correlational study was conducted with a sample of 232 respondents. The methodology included the application of a data collection instrument and descriptive and inferential statistical analyses. The most important results showed that 75% of respondents rated the achievement of program goals as regular, and that there is a positive and significant correlation (r=0.589; p<0.0001) between nursing staff performance and the achievement of these goals. It is concluded that the performance of nursing staff directly influences the achievement of goals of the Budget Program oriented to early childhood development in Loreto.